The National Plan of education Brazilian (2014-2024) and challenges for local development (Research, Society and Development, 2018)
The objective of the article is to analyze the Brazilian Education Plan (2014-2024) through the panorama of its guidelines and goals in terms of challenges for local development. This qualitative research collects dates from secondary sources such as documents and statistical data. The results of the research demonstrate two groups of challenges, the State and the State-Society interaction. In the first group, the eradication of illiteracy and interorganizational governmental interaction is highlighted. The second highlights public transparency and citizen participation in the implementation and management of the plan at the local level. A process of national planning of public policies becomes local development to the extent that the State and the Society increase goals and reach them democratically.